Development of the Chop Instrument in Table Tennis - Suhermon, Suhermon; Arisman, Arisman; Hendryanto, Ferri; Siska, Siska; Tofikin, Tofikin; Indah, Debby (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2023)
The purpose of this research is to make a chop meter for table tennis. This research method is research and development or Research and Development (R&D). The population and sample in this study were 20 PTM Pasir Pengaraian table tennis athletes. The research was carried out on February 13, 2023, by giving a questionnaire to 2 media experts and two material experts. The first test of Chop on March 5, 2023, and the second on March 7, 2023, tests the instruments reliability. The Criteria Test uses the results of the jurys assessment in the form of an assessment matrix to be carried out on March 6, 2023, to find the validity of the test. This study involved the first and second test samples of 20 Pasir Pengaraian PTM athletes, using data collection methods with questionnaires and tests. The study results were obtained from material experts 87.70% and 94% (very appropriate) and media experts 91% and 89.80% (decent) validity 0.91 and reliability 0.87, indicating validity and reliability based on the Kirkendall category